Ambidextrous working in health and social care services: A configurational view. Issue 6 (December 2020) - Harris, Martin; Wood, Geoffrey
Abstract: This study evaluates how middle and front-line managers contribute to organizational ambidexterity through their engagement with long-standing organizational dilemmas, supplementing earlier senior management focused work. Based on a multi-level exploratory study conducted within the UK health and social care sector, we investigate how middle and front-line managers were able to work on a collective and redistributive basis to address the tension between exploratory and exploitative innovation. Middle managers served as 'horizontal integrators' facilitating the emergence of shared understandings, learning capabilities and the distribution of knowledge-based resources, a process shaped by the constraints and opportunities provided by the broader intra-corporate environment. We conclude that the transition to ambidextrous working was impeded by restrictive bureaucratic dimensions, and facilitated by a distributed pattern of interaction, shared responsibility and more empowering bureaucratic forms.